Model Kepemimpinan Petrus dalam Kisah Para Rasul: Perubahan Karakter dan Pengaruh Roh Kudus dalam Kepemimpinan Awal Gereja - Picasaouw, Agus; Sitompul, Berkat; Andika Paulus Setiabudi; Joko Priyono (Sekolah Tinggi Teologi Trinity Parapat, 2025)
The contemporary church faces a critical need for effective spiritual leadership amidst internal and external challenges. This study aims to analyze the formation process, the empowerment by the Holy Spirit, and the crisis response of the Apostle Peter, and to establish its profound relevance for spiritual leadership today. Employing a qualitative-descriptive method with a biblical and theological literature analysis approach, this research highlights Peter's character transformation from an impulsive individual into a visionary leader, a change inextricably linked to the central role of the Holy Spirit in equipping him with boldness, wisdom, and authority. The study will also examine Peter's leadership response to internal crises and external conflicts faced by the early church, including issues of integrity, persecution, and theological debates. Ultimately, Peter's model of spiritual leadership provides timeless principles concerning leader formation, the importance of divine empowerment, and resilience in confronting challenges, which are highly relevant for contemporary Christian leadership.